Assessment of small fiber neuropathy and distal sensory neuropathy in female patients with fibromyalgia - Hong Ki Min; Sun Im; Geun-Young Park; Su-Jin Moon (The Korean Journal of Internal Medicine)
Background/Aims We investigated sudomotor dysfunction, small fiber neuropathy (SFN), and their clinical significance in female fibromyalgia patients. Methods Fibromyalgia patients and healthy controls (HCs) were recruited. Clinical and laboratory data were measured. Electrochemical skin conductance (ESC) values of hands and feet were assessed by SUDOSCAN. Additionally, several other methods were employed, including nerve conduction study (NCS), electromyography (EMG), and questionnaires. Spearman correlation coefficient was calculated to identify factors associated with ESC values of SUDOSCAN. Results Twenty-two female fibromyalgia patients and 22 female HCs were recruited. The fibromyalgia group had lower EQ5D and higher Toronto Clinical Neuropathy scores than the HC group. Most of the EMG/NCS findings of motor and proximal sensory nerves were comparable between the fibromyalgia and HC groups, whereas sensory nerve action potential amplitudes of distal sensory nerves were significantly lower in the fibromyalgia group. Mean ESC values of hands and feet were significantly lower in the fibromyalgia group than in the HC group (57.6 ± 16.2 vs. 68.8 ± 10.3 μS, p = 0.010 for hands, 64.9 ± 11.5 vs. 72.0 ± 8.2 μS, p = 0.025 for feet, respectively). Moderate to severe SFN was more common in the fibromyalgia group (68.2%) than in the HC group (68.2 vs. 50%, p = 0.019). Fibromyalgia disease duration was significantly correlated with the ESC values of hands/feet, and tricyclic antidepressant (TCA) responders had higher ESC values than non-responders. Conclusions SFN was commonly detected in fibromyalgia patients who had normal EMG/NCS findings and was more severe in fibromyalgia patients with longer disease duration. SUDOSCAN may predict response to TCA therapy.